The Effect of Digital Electronic Anti Smoking Campaigns on Adolescents' Perceptions and Behaviors in Middle Schools - Warijan; Nuraini (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
The increasing use of e-cigarettes among adolescents poses a serious public health challenge. This study aims to analyze the effectiveness of a digital-based anti-e-cigarette campaign on changes in knowledge, attitudes, and behavioral intentions of high school adolescents. The method used was a quasi-experimental pre-test–post-test control group design, involving 240 students divided into treatment and control groups. The intervention, a digital campaign through popular social media platforms (Instagram, TikTok, and WhatsApp), was implemented for four weeks, with content consisting of short videos, posters, and infographics.The results showed a significant increase in the treatment group compared to the control group. The average knowledge score increased by ±19.3 points, negative attitudes toward vaping increased by ±1.2 points, and healthy behavior intentions increased by ±1.3 points (p < 0.001). Inferential analysis using paired t-tests, independent t-tests, and ANOVA confirmed that these differences were due to the digital campaign intervention, with a significant contribution to the variability of change (partial η² 0.37–0.41). Furthermore, qualitative findings from focus group discussions revealed that the digital content was considered engaging, easy to understand, and capable of motivating adolescents to refuse vaping, although some respondents considered the campaign duration too short.In conclusion, digital campaigns have proven effective in improving health literacy, shaping negative attitudes toward e-cigarettes, and strengthening healthy behavioral intentions in adolescents. Digital-based educational strategies can be a relevant, adaptive, and potentially integrated preventive approach into broader public health programs.